Botanical characteristics and phytochemical analysis of Eucalyptus citriodora leaves - Dinh , Quang Dương; Huynh, Lời; Nguyen , Hồng Sơn; Vo , Văn Lẹo (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Lemon-scented gum (Eucalyptus citriodora Hook. Syn.: Corymbia citriodora (Hook.) K.D.Hill & L.A.S.Johnson) is a tree species primarily distributed in Vietnam and other countries. Lemon-scented gum was introduced to Vietnam in the 1960s and is cultivated sporadically from the North to the South (Vinh Phuc, Quang Ninh, Long An, and other provinces). The leaves contain essential oils with a pleasant aroma. The oils have strong antibacterial properties, so they are useful as antiseptics in the treatment of upper respiratory infections and certain skin diseases. Additionally, they are used in cosmetic, soap production, cleaning agents, skin disinfectants, and insect repellents. Currently, there has been no investigation of botanical characteristics or chemical analysis in Vietnam. The aim of this study is to determine a botanical characteristics and preliminarily screening the chemical constituents in the leaves of Eucalyptus citriodora.